2022
DOI: 10.3390/ani12030399
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lncRNA Expression in the Uterus between Periods of Embryo Implantation and Labor in Mice

Abstract: Uterine function during pregnancy is regulated mainly by progesterone (P4) and estrogen (E2). Serum P4 levels are known to fluctuate significantly over the course of pregnancy, especially during embryo implantation and labor. In this study, pregnant mice at E0.5, E4.5, E15.5, and E18.5 (n = 3/E) were used for an RNA-Seq-based analysis of mRNA and lncRNA expression. In this analysis, 1971 differentially expressed (DE) mRNAs, 493 known DE lncRNAs, and 1041 novel DE lncRNAs were found between E0.5 and E4.5 at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…In this study, we found that Hand2os1 was highly expressed in the luteal cells of mice during embryo implantation and delivery. This is consistent with the results of a previous study, in which some lncRNAs were found to play a role in embryo implantation and labor through immune responses [25]. These results suggest that Hand2os1 may be involved in embryo attachment and delivery mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that Hand2os1 was highly expressed in the luteal cells of mice during embryo implantation and delivery. This is consistent with the results of a previous study, in which some lncRNAs were found to play a role in embryo implantation and labor through immune responses [25]. These results suggest that Hand2os1 may be involved in embryo attachment and delivery mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, m6A modification is widely occurred in many other RNA species [43]. Notably, some long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) also play important roles in uterus during early pregnancy [44, 45]. It is highly possible that these noncoding RNAs are also subject to epigenetic m6A regulation.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that lncRNAs play an influential role in the development of a variety of tissues. For instance: heart ( Klattenhoff et al, 2013 ), liver ( Bu et al, 2020 ), testis ( Mishra et al, 2021 ), kidney ( Sun et al, 2020 ), Mammary gland ( Xu et al, 2018 ), brain ( Ang et al, 2020 ), uterus ( Zhao et al, 2022 ), and skin ( Zhao et al, 2021 ). There also be several lncRNAs related to muscle development and fat deposition have been reported, such as lncRNAs that related with muscle development including lnc403 ( Zhang et al, 2020 ), lnc-H19 ( Xu et al, 2017 ) and lncMD ( Sun et al, 2016 ), lncYYW ( Yue et al, 2017 ), and lncRNAs with fat deposition including lnc-BADLNCR1 ( Cai et al, 2020 ), lncCCPG1 ( Kang et al, 2020 ), and lncRNA ADNCR ( Li et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%